Pengaruh Orientasi Pasar dan Karakteristik Pasar serta Kreativitas terhadap Inovasi dan Kinerja Pemasaran Perusahaan Kosmetik di Provinsi Jawa Timur - Imam Suroso (Jurnal Aplikasi Manajemen, 2012)
The study aimed to investigate the effects of market orientation, market characteristics, and creativities on the innovation and marketing performances of the cosmetics Firms in East Java Province. The study was a confirmatory carried out by testing several hypotheses in order to figure out the causal relationship of all the above variables. The data were collected from the entire population of 37 cosmetics firms, registered as the members of the Indonesian Association of Cosmetics Firms or Persatuan Perusahaan Kosmetik Indonesia (PERKOSMI), East Java Chapter. These companies were also registered in the Food and Drugs Control Agency of the Republic of Indonesia (BP POM RI). The study employed complete enumeration or census method, hence, sample and sampling technique were not required. The validity of the research instrument was ensured by using construct validity, of which only items with positive correlation coefficient higher than 0.30 were included. Whereas, the reliability of the research instrument was determined by using Cronbach Alpha and items were considered reliable only when their values were higher than 0.60. The obtained data were, then, analyzed by using path analysis. The results showed that market orientation, market characteristics, and creativities had direct, positive and significant effects on the innovation of the cosmetics firms in East Java. Market orientation, market characteristics and innovation had direct, positive and significant effects on the marketing performances of the cosmetics firms. Surprisingly, creativities had no significant direct effects on the marketing performances of the cosmetics firms.Keywords: Market Orientation, Market Characteristics, Creativities, Innovation, Marketing Performances of Cosmetic Firms